IoT Approach to Stick for Elderly People - Ro, Cheulwoo; Kim, Taehee; Yoon, Jangwon; Ju, Mingyu (IJRDO -Journal of Computer Science Engineering, 2016)
An approach to a transformation of a passive stick into an IoT stick that could communicate a user’s smartphone thus beyond. Once a device is connected to a smartphone, then the capacity of connectivity drastically expands. Any falling-off accidents by the stick user, the elder, is detected by motion sensing mounted on our stick triggers a generation of an alarm that is notified to a remote guardian over the network. In addition, heartbeat sensing and step counting are implemented to assist the user to monitor the health condition. The stick can also be used as a gaming stick for helpful exercise and gaming.